Cubitus interruptus acts to specify naked cuticle in the trunk of Drosophila embryos. - Angelats, C.; Gallet, A.; Therond, P.; Fasano, L.; Kerridge, S. (Developmental Biology, 2002)
One function of the Wingless signaling pathway is to determine the naked, cuticle cell fate choice in the trunk epidermis of Drosophila larvae. The zinc finger protein Teashirt binds to the transactivator domain of Armadillo to modulate Wingless signaling output in the embryonic trunk and contributes to the naked cell fate choice. The Hedgehog pathway is also necessary for the correct specification of larval epidermal cell fate, which signals via the zinc finger protein, Cubitus interruptus. Here, we show that Cubitus interruptus also has a Wingless-independent function, which is required for the specification of the naked cell fate; previously, it had been assumed that Ci induces naked cuticle exclusively by regulation of wg. Wg and Hh signaling pathways may be acting combinatorially in the same, or individually in different, cells for this process, by regulating common sets of target genes. First, the loss of the naked cuticular phenotype in embryos lacking cubitus interruptus activity is very similar to that induced by a late loss of Wingless function. Second, overexpression of Cubitus interruptus causes the suppression of denticles (as Wingless does) in absence of Wingless activity in the anterior trunk. Using epistasis experiments, we conclude that different combinations of the three proteins Teashirt, Cubitus interruptus, and Armadillo are employed for the specification of naked cuticle at distinct positions both along the antero-posterior axis and within individual trunk segments. Finally, biochemical approaches suggest the existence of protein complexes consisting of Teashirt, Cubitus interruptus, and Armadillo.